An Alternative to the Adversarial: Studies on Challenges of Court-appointed Experts - Zhuhao Wang (Wolters Kluwer Medknow Publications, 2016)
At present, experts have become a mainstay of modern litigation, although criticisms suggest that the problems of how to fit expert knowledge comfortably into the method of adversarial fact-finding are numerous, significant, and without simple solutions. Concerns about partisanship and lack of scientific competence by adjudicators to evaluate contradictory expert testimony have been widely recognized in the traditional use of party-called expert witnesses. While such concerns cannot be wholly ameliorated, there may be alternative mechanisms that can help. One solution would be to call for the use of neutral court-appointed experts, to create a nonpartisan source of expert knowledge. A system of neutral court-appointed experts is an advisory tribunal to the court that could deliver "those general truths, applicable to the issue, which they may treat as final and decisive." However, no matter in which country, the choice of appointing neutral experts still seems to be a rare option for trial judges to consider and exercise. An obvious question would be: Why are neutral experts not used more frequently at trial? This paper did a study on court-appointed experts, with a focus on challenges that such mechanism faces. Part I examines problems in the traditional use of expert witnesses in an adversarial system. Part II discusses the incentives to make greater use of court-appointed experts in a typical adversarial system and to what extent such mechanism would solve difficulties within the traditional use of party-called expert witnesses. Part III further explores and analyzes obstacles that a typical neutral expert system nowadays encounters when it operates in practice. Taking all analysis together, Part IV makes an overall evaluation of the mechanism of court-appointed experts.